Genotypes for Antimicrobial Resistance and their Phenotypic Expression in Staphylococcus aureus Strains - Maribel Castellano González; Armindo Perozo Mena; Ana María Parra; Messaria Ginestre Pérez; Gresleida Rincón Villalobos (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Antimicrobial resistance was determined for 106 S. aureus strain isolates from patients treated in the Bacteriological Reference Center at the University Hospital Autonomous Service, Maracaibo, during the first trimester of 2009, using phenotypic and genotypic methods. Culture, isolation and identification were performed following conventional methodology. Phenotypically, 103 strains (97.17%) were resistant to penicillin G; 54 (50.94%) to methicillin; 43.39% to erythromycin (46) and 34.91% (37) to gentamicin. In addition, 13 (12.26%) were intermediate to erythromycin. Genotypically, 90 strains (84.91%) carried the blaZ gene through the polymerase chain reaction (PCR); 53 (50%) carried the mecA gene; only 10 (9.43%) harbored the gene aac(6')/aph(2''); the gene ermA was detected in 41 isolates (38.68%) and msrA in 17 (16.04%). The discordant results were: (1) A mecA-negative, but methicillin-resistant strain, which proved blaZ-positive and hyper-productive of B-lactamases; (2) An erythromycin-resistant strain, negative for ermA, B, C and msrA genes, and; (3)Twenty-six gentamicin-resistant strains, negative for aac(6')/aph(2''). The phenotypes and genotypes of antimicrobial resistance are related; however, there is a marked variability in the genetic determinants for resistance, which undoubtedly affects phenotypic expression. For oxacillin and, to a lesser degree erythromycin, there is a good match between the resistance phenotypes and genotypes found, noting the greatest discrepancy in the aminoglycosides and penicillin G.